2010
DOI: 10.1002/ejic.201000860
|View full text |Cite
|
Sign up to set email alerts
|

Di(2‐pyridyl) Ketone Complexes of CuI‐ and CuII‐Containing Iodide and Thiocyanate Ligands: An Unusual Case of a Mixed‐Aldol Condensation

Abstract: Complexes containing di(2‐pyridyl) ketone (dpk) as a bi‐ (N,N) and tridentate (N,N,O) ligand have been synthesised1,2 and characterized by spectral and structural studies. Products 1 and 2 are polymorphs of the polymeric copper(I) complex [Cu(dpk)(NCS)]n containing dpk with thiocyanate anions which bridge to form a one‐dimensional continuous polymer chain. The novel dinuclear copper(II) complex [Cu2(dpk·acetone)2(NCS)2] (3) was formed when 1 and 2 were allowed to stand in the supernatant. In this instance it a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Complex 1 crystallizes in the triclinic space group P ı and is a neutral molecular compound consisting of centrosymmetric Cu 2 (m-I) 2 units with the separation of 2.5855(8) Å between the two Cu(I) centers. This distance is close to that observed in related complexes like bis(m-iodido)-bis(2,2 0 -bipyridine)-di-copper(I) (2.579 Å) [32] or bis(m-iodido)-bis(di-2-pyridylketone)-dicopper(I) (2.547 Å) [33]. The inversion center is within the CuI 2 Cu bridge.…”
Section: Description Of the Crystal Structure Of [Cu(qbtz)(m-i)] 2 (1)supporting
confidence: 84%
“…Complex 1 crystallizes in the triclinic space group P ı and is a neutral molecular compound consisting of centrosymmetric Cu 2 (m-I) 2 units with the separation of 2.5855(8) Å between the two Cu(I) centers. This distance is close to that observed in related complexes like bis(m-iodido)-bis(2,2 0 -bipyridine)-di-copper(I) (2.579 Å) [32] or bis(m-iodido)-bis(di-2-pyridylketone)-dicopper(I) (2.547 Å) [33]. The inversion center is within the CuI 2 Cu bridge.…”
Section: Description Of the Crystal Structure Of [Cu(qbtz)(m-i)] 2 (1)supporting
confidence: 84%
“…Recent experiments have demonstrated that, when metal ions are present, other nucleophiles (e.g., the anions of acetonitrile and acetone, pyrazolates, bisulfate, and anionic secondary amino acids) are prone to attack the CO carbon of the ligand; these new molecules can be regarded as second-generation di(2-pyridyl) ketone ligands. 7,17,19,33,39,40,44 The coordination chemistry of di(2-pyridyl) ketone has been extensively studied with 3d-, 4f-, 3d/4f-, and 5f-metal ions but has been less investigated with those occupying the p block. Over the past few years, we have been making an effort to build a "periodic table" of metal ions with ligands based on (py) 2 CO 21 and herein we are glad to complete the blank space of indium.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Our group and others have had an intense interest over two decades or so in the reactions of coordinated ligands represented as A-CO-A, A-CO-CO-A, A-CO-A-CO-A, and A-CO-B, with A and B being donor and nondonor groups, respectively. The ligand studied most in depth is di­(2-pyridyl) ketone, (py) 2 CO, shown in Scheme . , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a commonly utilized ligand for metals, and numerous studies have investigated its interactions with metal ions. Mononuclear transition metal complexes of the dpk ligand were isolated when it acts a nitrogen bidentate ligand; mostly polynuclear or cluster transition metal complexes were expected if the carbonyl oxygen atom bonded to the metal center. The neutral dpk molecule can act as a bidentate ligand by forming bonds through the N, O or N, N atoms. Alternatively, it can be a tridentate ligand by forming additional bonds through the N, N, and O atoms. Moreover, when coordinated to M-centers, the OC group was subjected to nucleophilic addition reactions, such as the addition of water, revealing the formation of its hydrated gem-diol or alcohol, resulting in alcoholate dpk.ROH formation. Afterward, dpk can undergo an in situ procedure to convert into another ligand type, a transformation that cannot be accomplished by traditional organic methods. , In this work, the carbonyl of ketone in (dpk)­PdX 2 complex undergoes alcoholation in the existence of ROH (e.g., ethanol), an “ethanolated” (dpk·EtOH)­PdX 2 hemiketal complex was formed.…”
Section: Introductionmentioning
confidence: 99%